An SNP in protamine 1: a possible genetic cause of male infertility?. Issue 4 (30th September 2005) - Iguchi, N; Yang, S; Lamb, D J; Hecht, N B
Abstract : Gene targeting of the sperm nuclear proteins, the protamines, in mice leads to haploinsufficiency, abnormal chromatin compaction, sperm DNA damage, and male infertility. In order to investigate whether changes in amount or structure of the protamines could be a cause of human infertility, we sequenced the protamine genes of infertile men whose sperm appeared phenotypically similar to those of protamine deficient mice. We identified a heterozygous single nucleotide polymorphism (SNP) in the protamine ( PRM1 ) gene in three infertile men (10% of the total infertile men analysed). This SNP disrupts one of the highly conserved arginine clusters needed for normal DNA binding. To rapidly screen for this SNP in infertile patients, we developed a simple PCR restriction fragment length polymorphism assay. This is the first report of a SNP in the PRM1 gene that appears associated with human male infertility.